Answer:
(f + g)(x) = x² + x - 4
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Algebra I
- Terms/Coefficients
- Functions
- Function Notation
Explanation:
Step 1: Define
f(x) = 1 - x
g(x) = x² + 2x - 5
(f + g)(x) is f(x) + g(x)
Step 2: Solve
- Substitute in functions: (f + g)(x) = (1 - x) + (x² + 2x - 5)
- Combine like terms (x): (f + g)(x) = x² + x - 5 + 1
- Combine like terms: (f + g)(x) = x² + x - 4